The Acceptability of Participatory Banking Products by SMEs: A Conceptual Framework - Hachimi, Amina; Salahddine, M. My Abdelouhab (International Journal of Economics and Financial Issues, 2019)
Designed to contribute to the development of the real economy, the Islamic banking sector has grown significantly in the world during the last 40 years due to its ethical, religious and solidarity dimensions. It is set up to boost the banking system, to meet the needs of unmet customers and to give new hope to SMEs facing difficulties in accessing conventional bank financing. Islamic banks can contribute to the development of these companies and satisfy their financial needs. This article discusses the different factors influencing the decision of SME managers to adopt financing by participatory banks products. In this sense, the conceptual model presented is intended to study the level of acceptability of the participatory banks products by the SMEs starting from the application of the decomposed theory of planned behavior and the task-technology fit model. Keywords: SME, Participatory banking products, Acceptability. JEL Classifications: D22, G20, O16 DOI: https://doi.org/10.32479/ijefi.8227